Re-innervation of the Denervated Dentate Gyrus by Sprouting Associational and Commissural Mossy Cell Axons in Organotypic Tissue Cultures of Entorhinal Cortex and Hippocampus - Del Turco, Domenico; Paul, Mandy H.; Beeg Moreno, Viktor J.; Hildebrandt-Einfeldt, Lars; Deller, Thomas (Frontiers in Molecular Neuroscience, 2019)
Collateral sprouting of surviving axons contributes to the synaptic reorganization after brain injury. To study this clinically relevant phenomenon, we used complex organotypic tissue cultures of mouse entorhinal cortex (EC) and hippocampus (H). Single EC-H cultures were generated to analyze associational sprouting, and double EC-H cultures were used to evaluate commissural sprouting of mossy cells in the dentate gyrus (DG) following entorhinal denervation. Entorhinal denervation (transection of the perforant path) was performed at 14 days in vitro (DIV) and associational/commissural sprouting was assessed at 28 DIV. First, associational sprouting was studied in genetically hybrid EC-H cultures of beta-actin-GFPtg and wild-type mice. Using calretinin as a marker, associational axons were found to re-innervate almost the entire entorhinal target zone. Denervation experiments performed with EC-H cultures of Thy1-YFPtg mice, in which mossy cells are YFP-positive, confirmed that the overwhelming majority of sprouting associational calretinin-positive axons are mossy cell axons. Second, we analyzed associational/commissural sprouting by combining wild-type EC-H cultures with calretinin-deficient EC-H cultures. In these cultures, only wild-type mossy cells contain calretinin, and associational and commissural mossy cell collaterals can be distinguished using calretinin as a marker. Nearly the entire DG entorhinal target zone was re-innervated by sprouting of associational and commissural mossy cell axons. Finally, adenoviral tracing of newly formed associational/commissural axons revealed a rapid post-lesional sprouting response. These findings demonstrate extensive and rapid re-innervation of the denervated DG outer molecular layer by associational and commissural mossy cell axons, similar to what has been reported to occur in juvenile rodent DG in vivo.